Translation for Israeli television: the reflection of a hybrid identity - Weissbrod, Rachel (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Broadcasting in today ’s world is characterized by the tensions between competing entities, including the nation-state, the agents of globalization as well as national and other minorities. This article sets out to describe these tensions as manifested in translation for Israeli TV, focusing on the relations between Hebrew – the main and most ideologically protected language of Israel – and two minority languages, Arabic and Russian. The latter represent groups that are similar in size but differ greatly in that only the former seeks acknowledgement as a national minority.